PENGGUNAAN DOMPET DIGITAL SEBAGAI BENTUK DIGITALISASI MASYARAKAT DI KOTA DENPASAR - Nugraha Hanaya, Putu Satya; Suka Arjawa, I Gst. Pt. Bagus; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
ABSTRACT This study analyzes and explains how the reality of digitalization in the people of Denpasar in using digital wallets as a means of transactions and discrediting the impact of the use of digital wallets from the view of service providers and users located in Badung Market, UMKM, and Malls. The method used in this study is qualitative with descriptive type of explantative. The theory used is the network society of Manuel Castell. The theory explains the development of communication technology to be an important part of the network society for adaptability, this progress contributes to changing the nature of the economy, and society utilizes technology that has flexible characteristics. From the analysis conducted, Mall and UMKM have been fluent in making transactions, while in Badung Market between visitors and buyers are constrained by stuttering technology. The study also examined the social, economic, educational, and cultural impacts. Keywords: Digitization, Cashless Transactions, Digital Wallet, Network Society,Traditional Markets